The Meaningful Use of Electronic Health Records and Health Care Utilization. (July 2016) - Kern, Lisa M.; Edwards, Alison; Kaushal, Rainu; ,
This study sought to determine the effects on health care utilization of meaningful use (MU) of electronic health records (EHRs) compared to typical use of EHRs without MU. This was a cohort study of primary care physicians in New York State (2010-2011). A total of 7 outcomes (primary care visits, specialist visits, laboratory tests, radiology tests, emergency department visits, admissions and readmissions) and 11 potential confounders were considered. The study sample included 213 physicians (50% of whom had achieved MU) and 127 353 patients. There were 17 fewer primary care visits and 61 fewer laboratory tests for every 100 patients whose physicians achieved MU, compared with patients whose physicians did not achieve MU ( P < .05 for each). There were no differences for other outcomes. Achieving stage 1 MU was associated with fewer primary care visits and laboratory tests, suggesting that effects of MU are distinct from effects of typical EHR use.